Rancang Bangun Toko Gadget Berbasis Website Menggunakan Metode Scrum - Syifa Nur Rakhmah; Rizki Aulianita; Ganda Wijaya; Minda Septiani (INFORMATICS FOR EDUCATORS AND PROFESSIONAL : Journal of Informatics, 2023)
In this study, we conducted research at a gadget shop. The problem faced is the lack of offline marketing, resulting in a limited marketing network that relies on physical store sales. Reports are often delayed and files accumulate. SCRUM is a method used to develop online sales applications that can facilitate online product marketing and assist in managing transactions and reporting through existing systems. Development of PHP-based web applications with the CodeIgniter framework and MySQL database. In conclusion, the e-commerce website that was built did not replace the old system, but added an online system as a complement. The company previously only conducted offline activities. Based on the SCRUM method, this website helps companies expand their market and makes it easier for consumers to get information about products without having to come to a physical store. With an online sales system, Toko Gadget can modernize the transaction process and make it easier to generate sales reports.